Ocean Outpost The Future of Humans Living Underwater - Seedhouse, Erik.; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
Ocean Outpost is an undersea roadmap charting the future of man's exploration of Earth's last vast unexplored territory. To realize the goal of an extended human presence underwater a wealth of new technologies will be developed, such as new manned and unmanned submersibles, advanced propulsion systems, underwater rescue systems, decompression methods, and revolutionary physiological intervention strategies ranging from liquid ventilation to artifical gills. Some technologies will require quantum leaps forward in innovation, while others may appear even more daunting.
Preface -- Acknowledgements -- About the Author -- List of figures -- List of tables -- List of panels -- List of abbreviations and acronyms -- Section I Diving -- Chapter 1:No Limits freediving -- Chapter 2: Technical and saturation diving -- Part II Manned Submersibles and Undersea Habitats -- Chapter 3: Hardsuits -- Chapter 4: Manned Submersibles -- Chapter 5: Personal Submersibles and underwater flight -- Chapter 6: Ocean outpost -- Part III Ocean Exploitation -- Chapter 7: Deep-sea mining and energy exploitation -- Chapter 8: Ocean medicine -- Section IV Revolutionary Undersea Medicine -- Chapter 9: Liquid breathing and artificial gills -- Chapter 10: Becoming homo aquaticus -- Appendix -- Epilogue -- Index.
Keywords: Geography; Oceanography; Aquatic biology; Astrophysics; Science (General).; Earth Sciences; Oceanography; Popular Science, general; Extraterrestrial Physics, Space Sciences; Freshwater & Marine Ecology